THE EFFECT OF FINANCIAL REPORTING TRANSPARENCY ON FRIM VALUE ACCORDING TO THE ROLE OF PRODUCT MARKET COMPETITION - Omar Adeeb Qassim; Omar Adeeb Qassim (Scholars Digest Publishing, 2024)
This study aims to investigate the correlation between business value and transparency, considering the moderating impact of market rivalry. The Amman Stock Exchange includes all the companies that are listed as part of its statistical population. The systematic elimination strategy was used to choose the sample, and 36 firms from the years 2009 to 2021 made up the final sample size. A To evaluate the study hypothesis, a multivariate regression model based on pooled data was employed. The study's findings demonstrated that a company's worth is positively impacted by financial reporting openness. Furthermore, the findings demonstrate that the link between corporate openness and business value is unaffected by market rivalry.
Keywords: Financial Reporting Transparency, Firm Value, Market Competition.